Interaction of the community police officer with the structural units of the National Police and other entities that implement measures to prevent and combat domestic violence - О. О. Panova; M. O. Sherbyna (Law and Safety)
The purpose of the article was to determine the theoretical and legal basis for the interaction of the community police officer with the structural units of the National Police and other entities that implement measures to prevent and combat domestic violence.